2022
DOI: 10.1016/j.bios.2022.113974
|View full text |Cite
|
Sign up to set email alerts
|

All-solid-state SARS-CoV-2 protein biosensor employing colloidal quantum dots-modified electrode

Abstract: Rapid and reliable detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody can provide immunological evidence in addition to nucleic acid test for the early diagnosis and on-site screening of coronavirus disease 2019 (COVID-19). All-solid-state biosensor capable of rapid, quantitative SARS-CoV-2 antibody testing is still lacking. Herein, we propose an electronic labelling strategy of protein molecules and demonstrate SARS-CoV-2 protein biosensor employing colloidal quantum dots (CQDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…All analytical parameters are summarized in Table S2 . The analytical parameters obtained in this study and those of previously reported QD-based biosensors are compared in Table 1 32 38 , demonstrating the high sensitivity of the GAPDH sensor developed in this work.
Figure 4 Calibration plot using the stripping-current response.
…”
Section: Resultsmentioning
confidence: 66%
“…All analytical parameters are summarized in Table S2 . The analytical parameters obtained in this study and those of previously reported QD-based biosensors are compared in Table 1 32 38 , demonstrating the high sensitivity of the GAPDH sensor developed in this work.
Figure 4 Calibration plot using the stripping-current response.
…”
Section: Resultsmentioning
confidence: 66%
“…Here, R 1 , C, R ct , and Q represent the solution resistance, film capacitance, the charge transfer resistance, and the capacitance of the electrical double layer located at the electrode-electrolyte interface. With the increase of CK18 antigen concentration, the antibody and antigen specific binding reactions located at the electrode-electrolyte interface were more active, causing the change of modification layer on the WE, which may lead to the slight increase initially and subsequent decrease of R 1 (Figure 6c) [39]. When the CK18 antigen was added to the reaction system, the value of C decreased, but remained relatively stable with the increase of CK18 antigen concentration.…”
Section: The Sensing Mechanism Of the Electrochemical Biosensormentioning
confidence: 98%
“…327 The quantum tunneling and confinement behaviour in addition to the coulomb blockade present in quantum dots results in extraordinary charging response to alternating potential which can be exploited to develop SARS-CoV-2 sensors which can differentiate between normal and patient samples with nearly 90% accuracy. 328…”
Section: Inorganic Nanomaterials In Virus Sensing and Trackingmentioning
confidence: 99%